Education of the dentist in Brazil: the contribution of studies to professional practice - Maria Eneide Leitão de Almeida; Silvia Maria Nóbrega-Therrien; Filomena Maria da Costa Pinheiro; Maria Irismar de Almeida (Faculdade São Leopoldo Mandic, 2009)
To comment and discuss academic production in Brazil with regard to the education of dentists in the period between 1992 and 2005. Thestudy was conducted through online data base searches, bibliographic surveys in renowned national periodicals and master's dissertations.Data was collected from July to December 2005, and 13 studies on the subject were selected. It was shown that the majority of the studiesare concentrated in the Southern and Southeastern regions of Brazil. A change was noted in the education of dentists, which pointed out theneed for curricular alterations and teaching directed towards social needs, as well as the integration of teaching and service. From 1992 to 2005, there was a trend towards a predominantly technicist and curative education, transforming it into Dentistry directed largely towards the needs of the population, therefore assuming a more social nature with emphasis on health promotion. This social natureof Dentistry is perfectly suited to the Brazilian reality and it meets the demands of the Law of National Educational Guidelines and Bases/96 and the National Curricular Guidelines, as well as integrating dentists into the reality of the Family Health Program.